CSR DISCLOSURE AS A MODERATOR FIRM VALUE: A STUDY ON ENERGY SECTOR MANUFACTURING COMPANIES - Junika Halawa; Ilyona Risty (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
Investors' evaluation of a company's performance and prospects is reflected in its value. This study looks at how financial performance metrics, including firm size, profitability, leverage, and business operations, affect the value of energy businesses listed on the Indonesia Stock Exchange (IDX) between 2014 and 2022. Additionally, it looks into whether disclosure of corporate social responsibility (CSR) acts as a moderating element in these interactions. The study uses R-Studio software's panel data regression analysis with data from 28 companies, for a total of 224 observations. The findings suggest that whereas leverage, company size, and business operations do not significantly affect firm value, profitability does. Furthermore, there is no moderating effect of CSR disclosure on the association between business value and these financial performance metrics.